Creating Customer Loyalty Through Antecedents of Customer Satisfaction at Hoka-Hoka Bento Fast Food Restaurants - Luki Hidayat; Lia Amalia (Formosa Journal of Sustainable Research, 2023)
The purpose of this research is to understand the effects or consequences of perceived experience, perceived quality, perceived value, brand image, consumer satisfaction. Customer satisfaction and customer loyalty have been studied at Hokben. Participants in this study are people who buy and consume food from Hokben. This study uses a certain method in selecting a sample consisting of 157 individuals purposive sampling. The data was processed using the Lisrel structural equation model (SEM) method. The test results show that the hypothesis is accepted because the T-Value exceeds 1.96. That is, brand image has a positive effect on perceived value, perceived value has a positive effect on customer satisfaction, perceived experience has a positive effect on customer loyalty, brand image has a positive effect on customer loyalty and customer satisfaction has a positive effect on customer loyalty. Whereas in this study the results of Perceived experience have a negative effect on customer satisfaction, perceived quality has a negative effect on customer satisfaction, perceived quality has a negative effect on perceived value, brand image has a negative effect on customer satisfaction, perceived value has a negative effect on customer loyalty, because the value of T-Value which is less than 1.96